AN ACOUSTIC MEASUREMENT UNCERTAINTY EVALUATION: CASE STUDY OF ACOUSTIC INSTRUMENT CALIBRATION USING THE PORTABLE CALIBRATION SYSTEM - Dwisetyo, Bondan; Putri, Chery Chaen; Utomo, Fajar Budi; Prasasti, Ninuk Ragil; Hermawanto, Denny; Hapiddin, Asep (Instrumentasi, 2023)
The performance of an acoustic comparison coupler has been demonstrated. By carrying off a dual coupler method, this laboratory prototype is claimed to be utilized further as part of acoustic measurement instrument calibration and designed to support the traceability needs for the appropriate laboratory properly. To complete the requirement of calibration results provided by ISO/IEC 17025 : 2017, an evaluation and analysis of the uncertainty measurement related to this portable calibration system is strongly needed, where it has not been conducted yet. Therefore, this work aims to provide an evaluation and analysis of uncertainty measurement that is associated with sound level meter (SLM) calibration using the acoustic comparison coupler by the aforecited method through the statistical approximation by determining the major quantities such as standard uncertainty, combined uncertainty, and expanded uncertainty in accordance with JCGM - 100 : 2008. Moreover, a case study related to this instrument calibration is also discussed in this paper. This study also utilizes the class-1 of SLM as the reference instrument. Later, the obtained uncertainty values are compared to the established method that uses a multifunction acoustic calibrator in accordance with the acceptance limit values required by IEC 61672-1 : 2013.Keywords: uncertainty measurement, acoustic comparison coupler, dual coupler method, calibration, sound level meter